Marine exploitation and the arrival of farming: resolving the paradox of the Mesolithic-Neolithic transition in Denmark - T. Rowan McLaughlin; Harry K. Robson; Rikke Maring; Adam Boethius; Eric Guiry; Daniel Groß; Satu Koivisto; Bente Philippsen; Nicky Milner; Geoff Bailey; Oliver E. Craig (Quaternary Science Reviews, 2025)

Corrigendum to “Freshwater exploitation at Ajvide -Pitted ware culture fishing practises investigated through laser ablation facilitated strontium isotope analyses” [Quat. Sci. Rev. 344 (2024) 108967] - Beatrice Krooks; Adam Boethius (Quaternary Science Reviews, 2025)

Freshwater exploitation at Ajvide - Pitted ware culture fishing practises investigated through laser ablation facilitated strontium isotope analyses - Beatrice Krooks; Adam Boethius (Quaternary Science Reviews, 2024)

Advances and prerequisites for strontium isotope analyses through laser ablation in an aquatic context – Targeting Mid-Neolithic Baltic Sea harp seal (Pagophilus groenlandicus) mobility and breeding grounds - Adam Boethius; Jan Storå; Rudolf Gustavsson (Quaternary Science Reviews, 2024)

Mobility among the stone age island foragers of Jettböle, Åland, investigated through high-resolution strontium isotope ratio analysis - Adam Boethius; Jan Storå; Rudolf Gustavsson; Melanie Kielman-Schmitt (Quaternary Science Reviews, 2024)

Diachronic forager mobility: untangling the Stone Age movement patterns at the sites Norje Sunnansund, Skateholm and Västerbjers through strontium isotope ratio analysis by laser ablation - Adam Boethius; Mathilda Kjällquist; Melanie Kielman-Schmitt; Torbjörn Ahlström; Lars Larsson (Archaeological and Anthropological Sciences, 2022)
Strontium isotope ratios in human teeth from the three Swedish prehistoric Stone Age hunter-fisher-gathering societies Norje Sunnansund (Maglemose), Skateholm (Ertebølle) and Västerbjers (Pitted Ware Culture) were analysed with laser ablation to produce data on both individual movement patterns and societal mobility trends. The analyses of teeth from both Skateholm and Västerbjers displayed homogeneous ratios and corresponding mobility patterns, while the data from Norje Sunnansund showed larger variances with heterogenous strontium ratios and varied inter-individual mobility patterns. Correlation with the bioavailable baseline suggests that the size of the geographical areas, where human strontium ratios could have originated, was roughly comparable for all three sites. The teeth measurements were reflected within a 50-km radius of the surrounding landscape and the 25–75% data quartile matched with distances between 3 and 30 km from the sites, suggesting limited mobility ranges among aquatically dependent foragers from southernmost Sweden. By applying ethnographic analogies and site-specific contextual inferences, the results suggest that mobility ranges at Norje Sunnansund were likely not delimited by neighbouring group territories. This changed over time and an increasing territorialisation of the landscape may have influenced movement patterns and caused restrictions to the foraging activities at both Skateholm and Västerbjers.

Post-glacial human subsistence and settlement patterns: insights from bones - Dorothée G. Drucker; Anne Bridault; Adam Boethius (Archaeological and Anthropological Sciences, 2022)

Assessing laser ablation multi-collector inductively coupled plasma mass spectrometry as a tool to study archaeological and modern human mobility through strontium isotope analyses of tooth enamel - Adam Boethius; Torbjörn Ahlström; Melanie Kielman-Schmitt; Mathilda Kjällquist; Lars Larsson (Archaeological and Anthropological Sciences, 2022)
To evaluate the possibility of obtaining detailed individual mobility data from archaeological teeth, the strontium isotope ratios on 28 human teeth from three separate Early-Mid Holocene, Swedish, foraging contexts (Norje Sunnansund, Skateholm and Västerbjers) were analysed through laser ablation. The teeth/individuals have previously been analysed using traditional bulk sampled thermal ionisation mass spectrometry. To validate the conclusions regarding the archaeological teeth, a tooth from a modern man with a known background was also analysed. The result shows that all of the teeth display less than 0.4% discrepancy between the mean values of the laser ablation profiles and the previously published bulk data and 25 (89%) of the teeth display less than a 0.2% discrepancy. By calculating linear and polynomial trendlines for each ablated tooth, it was possible to illustrate a strong correlation for the transition pattern between the measurements when following a chronological sequence from the tip to the cervix. Such correlations were not reproduced when the data sequence was randomized. The analyses show that the chronologically sequenced ablation data fit with a transition between local bioavailable strontium regions, that the measurements do not fluctuate between extremes and that their values are not caused by end-member mixing. This indicates an increasing data resolution when reducing strontium isotope ratio averaging time by minimizing the sampling area. The results suggest strontium incorporation in human teeth can be measured on an ordinal scale, with a traceable chronological order to enamel mineralization when sampled from tip to cervix at an equal distance from the surface. Micro-sampling enamel is considered a valid method to assess prehistoric, but not modern, human mobility; laser ablation technology increases the amount of information obtained from a single tooth while rendering minimal damage to the studied specimen.